A Sala de Recursos Multifuncionais (SRM) como política educacional: metapesquisa de teses e dissertações (2008-2020) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
This Master’s thesis aimed to analyze the main theoretical-epistemological and methodological characteristics of Dissertations and Theses on the Multifunctional Resource Room (MRR) related to the field of Education Policy. Based on a pluralist epistemological perspective, contributions from authors of Inclusive Special Education were used (Boneti, 2006; Garcia, 2004; Glat; Pletsch; Fontes, 2007; Kassar, 2011; Mendes, 2006; Pletsch, 2009; Rodriguero, 2013; Sassaki , 2009), as well as from the field of Education Policy (Pavezi, 2018; Stremel, 2016; Vieira, 2011) and meta-research (Mainardes, 2021; Mainardes; Tello, 2015). Regarding the methodology, this study has a qualitative approach, using meta-research. Data collection was carried out in the Open Database of the Coordination for the Improvement of Higher Education Personnel (CAPES), considering all areas of publication, using the keywords [in Portuguese]: Sala de Recursos Multifuncionais and its acronym SRM [Multifunctional Resource Room, MRR]. Three hundred and one productions were catalogued, divided according to CAPES evaluation areas, totaling nine areas in which the works were highlighted. In the “Education” area, 222 productions were cataloged, 38 Doctoral Dissertations and 184 Master’s Theses, which were classified into the following categories: Inclusion (81 works); Teaching and learning (33); Specialized Educational Service (28); Education Policy (21); Special Education (14); Teacher Training (12); Curriculum (nine); Assistive Technology (six); Literacy (five); Giftedness (five); Planning (four); and Collaborative work (four). The 21 works on Education Policy were divided into two subgroups: MRR specific studies as Education Policy, with 18 productions (four Doctoral dissertations and 17 Master’s Theses); and works on MRR that are related to education policy, but they highlight other aspects (three works). The 18 works in the first group formed the analytical corpus for the meta-research. The main results were as follows: a) works were located in nine CAPES evaluation areas, which indicates that MRR has been the object of studies in areas other than Education; b) 14 works analyzed (88%) explain the epistemological perspective and the epistemological positioning; c) the concepts of Special Education and Inclusive Education were highlighted in all works, which characterizes the involvement with the area and the theoretical articulation of the researchers; d) regarding the levels of approach/abstraction, the majority of the works (67%) were classified as analytical, 22% as description and 11% as comprehension. The work develops to understand the MRR while the Educational Policy remains evident in official documents such as normative acts, Guidance Manual: Multifunctional Resource Room Implementation Program (Brazil, 2010), Technical Note n. 42, of SECADI/DPEE (2015), among others; presents a general objective to “support public education systems in organizing and offering specialized educational services and contributing to strengthening the process of educational inclusion in common education classes” (Brasil, 2007); and, it involves an allocation of resources from the Ministry of Education (Brazil, 2007). Like any other policy, the “MRR Implementation Program” is recontextualized in different school realities with different ways of putting the policy into action. The meta-research highlighted the need for theoretical and epistemological deepening in the works on the topic.
Keywords: Sala de Recursos Multifuncionais; Metapesquisa; Política Educacional; Multifunctional Resource Room; Meta-research; Education Policy.; CNPQ::CIENCIAS HUMANAS::EDUCACAO